FORMULATION AND EVALUATION OF HERBAL SCRUB GEL OF WALNUT SHELL - Snehal L. Mane; Baburao N.Chandakavathe; Deepak S. Bhosale, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
The main objective of present study was to prepare a Herbal scrub Gel. Herbal cosmeceuticals usually contain the plant parts which possess antimicrobial, antioxidant and anti aging properties. Herbal cosmetics are the safest product to use routine with no side effects and cosmeceuticals are the product which influences the biological function of skin. Different herbs are used for cleaning, beautifying the skin. In this preparation Walnut, cinnamon, rice powder, sandalwood, neem, turmeric and honey is used as active ingredients and incorporated into the gel which is prepared with carbopol of different grades. Other ingredients like propylene glycol, triethanolamine, methyl parahydroxy benzoate was added along with sodium lauryl sulfate into the gel. The prepared gel was evaluated for various parameters such as appearance, pH, viscosity, spreadability, washability, irritability. Formulations showed good spreadability, good consistency, homogeneity, appearance, pH, ease of removal. The formulation shows no redness, edema, inflammation and irritation during irritancy studies. These formulations are safe to use for skin and found to be satisfied with all required characterizations. Thus, the developed formulation can be used as an effective scrub for using it to bear a healthy and glowing skin.